Самораспространяющийся высокотемпературный синтез металлоуглеродных наноматериалов - Кускова, Наталья Ивановна; Челпанов, Дмитрий Ильич; Корзинова, Анна Николаевна (НТУ "ХПИ", 2017)
Реализованы процессы самораспространяющегося высокотемпературного синтеза (СВС) металлоуглеродных наноматериалов в волне горения, инициируемой разрядноимпульсным током. Выбрана экзотермическая система «алюминий + титан + политетрафторэтилен» для СВC карбида титана в процессе протекания сопряженных экзотермических реакций c образованием наноструктурного порошка карбида титана. Выбрана экзотермическая система «вольфрам + титан + углерод» для получения наноразмерных карбидов вольфрама и титана, в которой в качестве источника углерода используются порошки углеродных наноматериалов, синтезированные методом электроразрядной обработки углеводородов.

Processes of self-propagating high-temperature synthesis (SHS) of metal-carbon nanomaterials in a combustion wave initiated by a pulse discharge current are realized. Exothermic systems for SHS of metallocarbon nanomaterials are chosen. Powder mixture "aluminum + titanium + polytetrafluoroethylene" is proposed to use for SHS of titanium carbide via series of conjugated exothermic reactions. It is shown that nanostructured titanium carbide powder with nanocrystallites’ size of 35 nm is formed as a result of combustion of the mixture. Carbon nanomaterial powders which were synthesized by the electrodischarge processing of hydrocarbons are used to synthesize carbides of tungsten and titanium in the "tungsten + titanium + carbon" system with nanocrystallites’ size of 48.8 nm for TiC, 46 nm for W2C and 20.7 nm for WC.
Self-propagating high-temperature synthesis of metal-carbon nanomaterials
Keywords: разрядноимпульсное инициирование; карбид титана; карбид вольфрама; электроразрядная обработка; discharge initiation; titanium carbide; tungsten carbide; carbon nanocrystalline material